2016
DOI: 10.1177/2047487316631395
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with oral anticoagulant drugs restrained from patients with atrial fibrillation: An assessment in a geographically well-defined catchment area

Abstract: This is, to our knowledge, the first study to assess the reasons for restraining the use of OAC drugs in a geographically well-defined population including all hospital-based and non-hospital-based healthcare. Applying CHA2DS2-VASc and new strategies for OAC drugs to our study data indicated that between 72 and 88% of all patients with AF are eligible for treatment with OAC drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A 2010 survey of GPs in Sweden indicated that major reasons for withholding OAC therapy from high risk patients included a lack of medical indication, regained sinus rhythm and assumed poor patient compliance. 26 Nevertheless, there are clearly a large number of high risk patients in New Zealand primary care who should be using OACs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 survey of GPs in Sweden indicated that major reasons for withholding OAC therapy from high risk patients included a lack of medical indication, regained sinus rhythm and assumed poor patient compliance. 26 Nevertheless, there are clearly a large number of high risk patients in New Zealand primary care who should be using OACs.…”
Section: Discussionmentioning
confidence: 99%